Narrativas autobiográficas de professores iniciantes no ensino superior: trajetórias formativas de docentes do curso de Letras-Inglês - Cunha, Renata Cristina da (2014)
This work has as an object of study the academic process of teachers that are at the beginning of their careers starting from their oral and written autobiographical stories, motivated by the leading question: What experiences have the English teachers experienced before the teaching profession and in the beginning of their careers are configured as formative after they becoming Higher Education professionals? To respond to this leading question, there were stated the following objectives: General objective: To know and analyze the autobiographical stories of the English teachers that are working for UESPI in the English course, beginners in the higher education field about the formative experiences acquired before the teaching work and in the beginning of their careers. Specific objectives: 1) To describe and analyze the researched participants memories-reference revealing time, space and the context of formation and learning of the profession before entering the higher education; 2) To characterize and analyze the experiences lived by the interlocutors of the research when they started their careers of teaching in higher education; 3) To identify and discuss the effective reflections through the production of oral and written autobiographical narratives to reveal the experiences gathered by the research subjects all through their life trajectory. An autobiographical survey was carried on with a methodology of qualitative approach reaching out to the authors such as Clandinin and Connelly (1995, 2000), Bolívar (2002), Souza (2004, 2006a, 2006b), among others. Three English teachers collaborated with this study, all of them beginners in the career of higher education at UESPI, Parnaíba (PI). To achieve the objectives of this research, that was done through 2012, there were used the formation memorial, reflective letters and the interactive meetings. The content of the research corpus was analyzed based in Bardin s proposal (2006). The produced data were analyzed based on the theoretical approach studied about the fresh teacher, formative experiences of autobiographical stories, and they were organized around four key areas and their respective indicators: 1) First learning experiences: the experiences brought by each collaborator; 2) Schooling stories: school and university as formative environment; 3) Teaching formative experience: the practicing of teaching as a source of learning: 4) Autobiographical dialogues: Formative possibilities to work independently. The research interlocutors oral and written narratives confirmed that the formative process of each teacher is directly connected to its life trajectory that has guided the gathered learning and the developed practicing throughout their lifetime. What they bring to themselves is the formative experiences and memories-references that set apart the three protagonists of their own history.